OPTIMAL POWER FLOW: MODELING AND SIMULATION, SOLUTION METHODS, AND ITS APPLICATION USING POWERWORLD SOFTWARE® - Didi Istardi (Jurusan Teknik Informatika, 2010)
Optimal power flow has been used to solve a large class of problems in the power industry, including planning, generation dispatch, and security constrained dispatch. The OPF problem can be described as the cost of minimization of real power generation in an interconnected system where real and reactive power, transformer taps, and phase-shift angles are controllable and a wide range of inequality constraints are imposed. It is a static and a nonlinear optimization problem. In this paper, we will try to see how the OPF is modeled and simulated using powerworld software®, and what solution methods can be used to implement the models. Applications of the optimal power flow methods will also be analyzed based on this software.